(untitled) (Journal of Computational Mathematics, 2018)
The exact pointwise estimation of the Hermite-Fejér interpolation process based on the zeros of the Jacobi polynomial P^(α,β)_n(x)(-1 ‹α,β ≤ 0) is given. The method employed is useful for other extended H-F interpolations also.